Acute Myeloid Leukemia as the Main Cause of Pancytopenia in Iranian Population - Jalaeikhoo, Hasan (Iran J Pathol, 2017)
BACKGROUND & OBJECTIVE: Pancytopenia is the reduction in the number of all 3 major cellular elements of blood and leads to anemia, leukopenia, and thrombocytopenia. A wide variety of etiologies result in pancytopenia including leukemia, aplastic anemia, and megaloblastic anemia. The current study identified the different etiologies of pancytopenia based on bone marrow examination in Iranian patients with pancytopenia. METHODS: A total of 683 cases of pancytopenia with various etiologies were selected for this retrospective study. Bone marrow biopsy was performed with the standard technique using Jamshidi needle. The inclusion criteria for patients with pancytopenia were hemoglobin (Hb) <10 g/dL, total leukocyte count (TLC) <4 x 10(9)/L, and platelet count <140 x 10(9)/L. RESULTS: In the present study acute leukemia was the first most common etiology detected in 235 (35.4%) patients in which acute myeloid leukemia (AML) comprised the majority of cases 142 (21.4%), followed by myelodysplastic syndrome (MDS) 100 (15%). In patients less than 20 years old, acute leukemia was also the commonest cause identified in 56 (57.7%) cases in which acute lymphoblastic leukemia (ALL) with 38.7% was the most common etiology; however in adults (>45 year old), AML accounted for the majority of cases 76 (53.5%). CONCLUSION: Since acute leukemia was the commonest etiology in both young and adults in which AML accounted for the majority of cases with pancytopenia in Iranian population, there was an urgent need to identify the underlying molecular or genetic mechanism of this malignancy for better further medical management and patients` survival.